Analisis Strategi Peningkatan Daya Saing Komoditas Kentang di Kabupaten Karo, Sumatera Utara - Hanna Silvia; Muhammad Syamsun; Lindawati Kartika (Institut Pertanian Bogor, 2015)
Asean Economic Community (AEC) has given a new challenges to Indonesia to maintain its products, include horticulture commodities, such as potato. One of potatoes production centers in Indonesia is Karo Regency, North Sumatera. The purpose of this study are to identify supply chain’s structures and internal-external factors to formulate strategies for increasing potato competitiveness in Karo Regency. Data analyzed by Descriptive analysis, TOWS, and Pairwise Comparison. The results of this study is there are four priority strategies for Karo Regency in increasing it competitiveness, such as: 1) Training farmers to improve farmer’s ability, independence, and institutional welfare through the establishment of Desa Percontohan; 2) Increasing the plant diseases treatment through the optimalization of agriculture clinic; 3) Improve farmer’s ability to work in collaboration with bussines partner through promotion of agricultural products; and 4) Increasing the development of potatoes’s superior seeds.